Continue study unlocks more opportunities - Sakinah, Abdullah (2022)
PAYA BESAR, 8 November 2022 - “Quality exposure, knowledge and evaluation are tickets for us to open up more opportunities for success in the future,” said Fatrus Bahari, 45, recipient of the Lifelong Learning Award (PSH), UMP Advanced at the UMP 17th Convocation Ceremony.